Cytogenetic and Molecular Characterization of Heterochromatin Gene Models in Drosophila melanogaster - Rossi, Fabrizio (Copyright © 2007 by the Genetics Society of America, 2007)
In the past decade, genome-sequencing projects have yielded a great amount of information on DNA sequences in several organisms. The release of the Drosophila melanogaster heterochromatin sequence by the Drosophila Heterochromatin Genome Project (DHGP) has greatly facilitated studies of mapping, molecular organization, and function of genes located in pericentromeric heterochromatin. Surprisingly, genome annotation has predicted at least 450 heterochromatic gene models, a figure 10-fold above that defined by genetic analysis. To gain further insight into the locations and functions of D. melanogaster heterochromatic genes and genome organization, we have FISH mapped 41 gene models relative to the stained bands of mitotic chromosomes and the proximal divisions of polytene chromosomes. These genes are contained in eight large scaffolds, which together account for ∼1.4 Mb of heterochromatic DNA sequence. Moreover, developmental Northern analysis showed that the expression of 15 heterochromatic gene models tested is similar to that of the vital heterochromatic gene Nipped-A, in that it is not limited to specific stages, but is present throughout all development, despite its location in a supposedly “silent” region of the genome. This result is consistent with the idea that genes resident in heterochromatin can encode essential functions.